Outdoor and indoor air microflora of academic buildings in Poznań - Stach, Alicja; Piotraszewska-Pająk, Alina; Stryjakowska-Sekulska, Maria; Filipiak, Marian; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Indoor and outdoor microflora in the environment of academic buildings in the centre of Poznań was investigated and presented in this paper. A high and differentiated microbiological contamination of both indoor and outdoor air was found. Dominating microflora consisted of filamentous fungi (up to 55% of the total number of microorganisms) whereas contribution of bacteria has not exceeded 40%. In the outdoor air the prevailing microorganisms included bacteria: Micrococcus and Bacillus and moulds: Cladosporium , Alternaria , Penicilium and Aspergillus . In the indoor air bacteria including Micrococcus , Staphylococcus , Serratia and Bacillus and moulds: Rhizopus , Penicilium, Aspergillus , Cladosporium and Alternaria were dominating. Some of the fungi found are associated with several allergic diseases and they can cause different health problems.